Advances in radical peroxidation with hydroperoxides - Bityukov, Oleg V.; Serdyuchenko, Pavel Yu.; Kirillov, Andrey S.; Nikishin, Gennady I.; Vil’, Vera A.; Terent’ev, Alexander O. (Beilstein Journal of Organic Chemistry, 2024)
Organic peroxides have become sought-after functionalities, particularly following the multi-tone consumption in polymer production and success in medicinal chemistry. The selective introduction of a peroxide fragment at different positions on the target molecule is a priority in the modern reaction design. The pioneering Kharasch–Sosnovsky peroxidation became the basic universal platform for the development of peroxidation methods, with its great potential for rapid generation of complexity due to the ability to couple the resulting free radicals with a wide range of partners. This review discusses the recent advances in the radical Kharasch-type functionalization of organic molecules with OOR fragment including free-component radical couplings. The discussion has been structured by the type of the substrate of radical peroxidation: C(sp3)–H substrates; aromatic systems; compounds with unsaturated C–C or C–Het bonds.
Keywords: C–H functionalization; oxidation; peroxidation; radical reactions; TBHP